Literature Review on The Use of Cloud-Based Learning for Islamic Religious Education - Desiana, Desiana; Koderi, Koderi; Jatmiko, Agus; Mustofa, Ihsan (Riviera Publishing, 2024)
Cloud-based learning shows a significant impact on Islamic religious education, especially in the use of Google Classroom. Several studies have examined the effectiveness of cloud-based learning programs in developing reflective thinking skills and increasing student learning motivation in Islamic religious education. In addition, the application of Google Classroom for distance learning has overcome problems related to the number of students in Islamic religious education subjects. The research also explores the use of cloud technology and ICT tools to improve the teaching of Islamic religious education and support personalized learning trajectories for students. Overall, the literature highlights the transformative potential of cloud-based learning and technology to revolutionize the learning experience in Islamic religious education. This research uses a systematic and comprehensive literature study method to analyze books, scientific articles and related sources that are relevant to the topic of cloud-based learning in the use of Google Classroom for Islamic religious education. The methodological framework includes the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for the identification and selection of eligible studies, as well as the use of well-known research quality assessment tools. Analysis results are synthesized to produce reports that are informative, well-organized, and context-rich.